2016
DOI: 10.1140/epjc/s10052-016-4399-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of elastic pp scattering at $$\sqrt{\hbox {s}} = \hbox {8}$$ s = 8  TeV in the Coulomb–nuclear interference region: determination of the $$\mathbf {\rho }$$ ρ -parameter and the total cross-section

Abstract: The TOTEM experiment at the CERN LHC has measured elastic proton-proton scattering at the centre-ofmass energy √ s = 8 TeV and four-momentum transfers squared, |t|, from 6 × 10 −4 GeV 2 to 0.2 GeV 2 . Near the lower end of the t-interval the differential cross-section is sensitive to the interference between the hadronic and the electromagnetic scattering amplitudes. This article presents the elastic cross-section measurement and the constraints it arXiv:1610.00603v1 [nucl-ex] 3 Oct 2016 2 imposes on the funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 43 publications
(88 reference statements)
8
75
0
Order By: Relevance
“…The real part was predicted to be small inside the cone at high enough energies. That is now confirmed by experimental data [25]. The ratio of real to imaginary part of forward pp-amplitude changes from 0.14 at ISR-energies to 0.1 at 13 TeV.…”
Section: The Elastic Differential Cross Sectionsupporting
confidence: 76%
“…The real part was predicted to be small inside the cone at high enough energies. That is now confirmed by experimental data [25]. The ratio of real to imaginary part of forward pp-amplitude changes from 0.14 at ISR-energies to 0.1 at 13 TeV.…”
Section: The Elastic Differential Cross Sectionsupporting
confidence: 76%
“…Although at the small transferred momenta interference of the hadronic phase with the Coulomb one can become prominent [47], the asymmetry (unlike the one for electron scattering) stays too small due to the large σ b . Thus the effects of the amplitude's phase are governed by width of the colliding beams.…”
Section: Jhep03(2017)049mentioning
confidence: 96%
“…A proper analysis of the elastic proton-proton collisions at the Large Hadron Collider (LHC) at √ s = 7 TeV by the TOTEM collaboration [44,45] has also shown that the real part of the amplitude can dominate for the large transferred momenta [46]. Finally, just a few months ago the TOTEM collaboration managed to estimate the amplitude's phase at √ s = 8 TeV in the interval of |t| from 6 × 10 −4 GeV 2 to 0.2 GeV 2 with a much better accuracy than before [47].…”
Section: Jhep03(2017)049mentioning
confidence: 99%
See 2 more Smart Citations